Neo-Liberal Educational Reform in Latin America - Susana López Guerra; Marcelo Flores Chávez (Universidad Autónoma de Baja California, 2006)
Using the argument that educational systems in Latin American are inefficient, political organizations and international financial institutions promoted reforms based on free market principles to modernize education in the region. Chile was used as a laboratory for these reforms, which were then applied to other Latin American countries. This paper analyzes the argument that educational quality is improved through competition-used as a strategy to privatize the educational system-by transferring its financing from public to private sources, to the detriment of the national system of education. Finally, this paper examines the modernization process and the failure of the free market model of the Mexican system of education.